Model Rekayasa Sosial Ekonomi Berbasis Masjid: Integrasi Pengelolaan Dana Umat dan Layanan Pendidikan di Tanimulya - Ganjar Santika; Khofifah, Nurul; Ikhlas Solihati; Tanti Rahayu; Ade Rohana (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to analyze the role of Al-Mujahidin Mosque in Tanimulya Village, Ngamprah District, West Bandung Regency, in socio-economic social engineering based on the management of community funds. The mosque functions not only as a place of worship but also as a center for community empowerment through the management of zakat, infaq, sadaqah, and waqf integrated with educational and social sectors. This research employs a qualitative approach using a case study method. Data were collected through observation, documentation, and literature review, including institutional data from Yayasan Bina Tani Mulya Al-Mujahidin (YBTMA). The findings indicate that Al-Mujahidin Mosque has successfully developed a community empowerment model through three main sectors: productive management of community funds, provision of affordable and quality formal and non-formal education, and implementation of social programs such as basic needs assistance and educational support for underprivileged communities. This study concludes that mosques have significant potential as community-based socio-economic development centers that contribute to improving social welfare. This model aligns with the principles of maqāṣid al-sharī‘ah, particularly in preserving religion, intellect, and wealth.